Numerical model of the geothermal regime on the Beaufort Shelf, arctic Canada since the Last Interglacial. Issue 4 (14th November 2013) - Taylor, Alan E.; Dallimore, S. R.; Hill, P. R.; Issler, D. R.; Blasco, S.; Wright, F.
Abstract [1] A finite element geothermal model is developed for the outer Mackenzie Delta‐Beaufort Sea shelf to predict permafrost evolution since the Last Interglacial 130–116 kaBP(cal). The purpose is to reconcile sparse observations of the depth and extent of ice‐bonded permafrost with sediment properties and the paleoenvironment. Sea level curves determine, as a function of time, areas of the shelf that were subaerially exposed, promoting permafrost aggradation, and areas that were submerged, promoting permafrost degradation. Assuming as a model starting point that a paleoclimate similar to today persisted through the Last Interglacial, permafrost subsequently aggrades in depth and advances seaward from the present shoreline to the shelf/slope bathymetric break by the Last Glacial Maximum (LGM) 26 kaBP(cal). Modeled permafrost exhibits reduced growth in depth and seaward progression that correlate with early and middle Wisconsin stillstands in sea level. Following the LGM and rise in sea level, offshore permafrost degrades and permafrost base rises 100 m to its present depth of 600 m. The offshore limit of modeled ice‐bonded permafrost lies at the 95 m isobath, within 1 km of the bathymetric shelf/slope break. The model replicates features of offshore permafrost body observed seismically and demonstrates that warm outflow from the Mackenzie River depresses the upper surface of offshore permafrost by tens of meters to the 20 m isobath. Although Pleistocene permafrost predated the Wisconsinan, the model demonstrates that the paleoenvironment of the last 125, 000 years is sufficient to develop the depth, seaward extent, and principal features of the permafrost body.